The First Nest Records of the Wasp Eumenes punctaticlypeus kostylevi (Hymenoptera, Vespidae, Eumeninae) and Notes on its Distribution in Crimea - Fateryga, A.V.; Matushkina, N.A. (Вестник зоологии, 2010)
Two nest records of the rare solitary wasp Eumenes punctaticlypeus kostylevi Kurzenko, 1976 are described for the first time. One non-completed nest was built in a stone surface and another one was attached to a bush stem; the latter one consisted of six cells. Nest cells are arranged in a cluster and have common internal walls. All cells are spirally disposed around the stem and theirs collars look at different directions. A male was reared in the first cell and three females in the second to fourth cells. Examination of the collection materials revealed that the distribution area of the species in Crimea embraces zones of Foothills and South Coast.